2007
DOI: 10.1002/jnr.21382
|View full text |Cite
|
Sign up to set email alerts
|

1,25‐dihydroxyvitamin D3 reverses experimental autoimmune encephalomyelitis by inhibiting chemokine synthesis and monocyte trafficking

Abstract: Multiple sclerosis (MS) is a complex neurodegenerative disease whose pathogenesis involves genetic and environmental risk factors leading to an aberrant, neuroantigen-specific, CD4+ T cell-mediated autoimmune response. In support of the hypothesis that vitamin D3 may reduce MS risk and severity, we found that vitamin D3 and 1,25-dihydroxyvitamin D3 (1,25-(OH)2D3) inhibited induction of experimental autoimmune encephalomyelitis (EAE), an MS model. To investigate how 1,25-(OH)2D3 could carry out anti-inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
111
0
4

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(118 citation statements)
references
References 44 publications
3
111
0
4
Order By: Relevance
“…However, in males and females, administering 1,25-(OH) 2 D 3 inhibited EAE induction and progression, and after disease establishment, induced EAE remission (30)(31)(32). In EAE, we found that 1,25-(OH) 2 D 3 did not inhibit pathogenic CD4 + T cell development or trafficking (32,33), but instead increased the sensitivity of pathogenic T cells to apoptotic signals within the CNS (33,34). These mechanisms required VDR expression in the pathogenic CD4 + T cells (11).…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…However, in males and females, administering 1,25-(OH) 2 D 3 inhibited EAE induction and progression, and after disease establishment, induced EAE remission (30)(31)(32). In EAE, we found that 1,25-(OH) 2 D 3 did not inhibit pathogenic CD4 + T cell development or trafficking (32,33), but instead increased the sensitivity of pathogenic T cells to apoptotic signals within the CNS (33,34). These mechanisms required VDR expression in the pathogenic CD4 + T cells (11).…”
mentioning
confidence: 73%
“…We previously found that 64% of CD4 + T cells in the inflamed spinal cord of mice with EAE underwent apoptosis within 18 h after 1,25-(OH) 2 D 3 was administered, but immune cell trafficking into the spinal cord was unchanged (33). Accordingly, we suggest that fewer CD4 + T cells were detected in the CNS of mice receiving vitamin D 3 or 1,25-(OH) 2 D 3 compared with placebo controls because of diminished T cell longevity.…”
Section: Discussionmentioning
confidence: 99%
“…If vitamin D3 is used, the beneficial effect predominates in females, likely via a potentiation by oestrogens [Spach and Hayes, 2005;Nashold et al 2009;Subramanian et al 2012]. Various immunological mechanisms have been reported to explain the vitamin D and calcitriol effects: an anti-inflammatory effect [Spach et al, 2004], actions on macrophages [Nashold et al 2000], on different types of cytokines [Cantorna et al 1998;Spach et al 2006;Pedersen et al 2007], on regulatory T lymphocyte cells (Tregs), lymphocyte T helper 1 (Th1), Th17 and Th2 [Mattner et al 2000;Muthian et al 2006;Chang et al 2010;Mayne et al 2011] and invariant natural killer T-cells (iNKTs) [Cantorna et al 2012]. Interestingly, with low VDR gene expression, EAE is facilitated, with an increase in Th1 and Th17, suggesting that, in a similar genetic situation in humans, the MS risk may be increased despite high ambient UV radiation (e.g.…”
Section: Multiplicity Of Vitamin D Actionsmentioning
confidence: 99%
“…However, the concentrations of 1,25D3 employed in many studies are often above the physiological range, bringing into question the physiological relevance of the effect of 1,25D3 on T cells. Nonetheless, modulation of CD4ϩ T cells by 1,25D3 is intriguing because several studies have demonstrated that 1,25D3 is capable of suppressing inflammation in vivo (7)(8)(9)(10).…”
mentioning
confidence: 99%